Prospective comparative study of tolerance to refractive errors after implantation of extended depth of focus and monofocal intraocular lenses with identical aspheric platform in Korean population - Son, Hyeck Soo; Auffarth, Gerd U. (BMC ophthalmology, 2019)
To evaluate the clinical outcomes of extended depth of focus (EDOF) and monofocal intraocular lenses (IOLs) that share identical aspheric platform and compare their visual acuity tolerance to postoperative refractive errors.